Sustainable cross-border cooperation? A case-study on the role of national minorities - Benczi, Melinda (Észak-magyarországi Stratégiai Füzetek, 2023)
Cross-border cooperation within the European Union is a cornerstone of regional integration, fostering collaboration and solidarity among Member States. This article explores the role of national minorities, specifically in the Romanian-Hungarian border region, as contributors to the territorial impact and sustainability of cross-border projects. While existing research highlights their potential as bridge builders, this study critically assesses the tools used for measuring impact and sustainability in cross-border initiatives, uncovering a gap in acknowledging the role of national minorities. Through a case study of Romanian Hungarian INTERREG projects between 2007-2020, this article sheds light on the nuanced relationship between national minorities and cross-border engagement. It underscores the need for further research, policy considerations, and emphasises that by harnessing the bridge-building potential of national minorities, they could be one of the guarantees for the cross-border projects’ enduring results as well as collaboration, strengthening regional unity and prosperity in the European Union.